Synthesis, structures and photophysical properties of copper(I) 2-(2-benzimidazolyl)-6-methylpyridine complexes with different diphosphine ligands. (24th November 2016) - Di, Bao-Sheng; Chen, Jing-Lin; Luo, Yan-Sheng; Zeng, Xue-Hua; Qiu, Lu; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui
Graphical abstract: A series of new mono- and binuclear Cu(I) 2-(2-benzimidazolyl)-6-methylpyridine complexes with five different diphosphine auxiliary ligands were synthesized and characterized, and all Cu(I) complexes exhibit good luminescence properties in solution and solid states, which are more markedly influenced by the P–Cu–P bond angle. Abstract: A series of new Cu(I) 2-(2-benzimidazolyl)-6-methylpyridine (Hbmp) complexes containing five different diphosphine auxiliary ligands have been synthesized and well characterized. It is revealed that all Cu(I) atoms display distorted N2 P2 tetrahedral geometries with distinct P–Cu–P bond angles regulated by diverse diphosphine ancillary ligands, in which Hbmp serves as a charge-neutral chelating ligand without the deprotonation of the benzimidazolyl-NH while the diphosphine ligand adopts a bridging or chelating coordination mode. It is demonstrated that all these Cu(I) complexes show a relatively weak low-energy absorption in solution and exhibit good luminescence properties in solution and solid states at room temperature, which are more markedly influenced by the P–Cu–P bond angle.